THE DIFFERENCE IN THE EFFECTIVENESS OF PROPRIOCEPTIVE EXERCISE AND ZIG-ZAG RUN EXERCISE TOWARD AGILITY IMPROVEMENT IN CHILDREN AGED 9-11 YEARS OLD IN ELEMENTARY SCHOOL 4 SANUR - Gita, Made Dwi Indah Permatahati; Andayani, Ni Luh Nopi; Sugiritama, I Wayan; Wiryanthini, Ida Ayu Dewi (Majalah Ilmiah Fisioterapi Indonesia; Vol 4 No 3 (2016): Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Agility is a person's ability to change the direction and position of the body quickly, effectively, and accurately in a short time without any sign of losing balance. This study with Pre and Post Test Two Group Design aims to compare Proprioceptive Exercise and Zig-zag Run Exercise in improving the agility of children aged 9-11 years in Elementary School 4 Sanur. The amount of samples is 16 children that divided to 2 groups. The average difference in agility improvement on the Proprioceptive Exercise group was 3.46 seconds and Zig-zag Run Exercise group was 4.98 second with independent sample T-test result obtained p=0.003 (p<0.05). It can be concluded that Zig-zag Run Exercise is better for improving agility than Proprioceptive Exercise of children aged 9-11 years in Elementary School 4 Sanur. Keywords: Agility, Proprioceptive Exercise, Zig-zag Run Exercise, Shuttle Run Test.